Epilepsy after perinatal stroke with different vascular subtypes. Issue 2 (2nd March 2018) - Laugesaar, Rael; Vaher, Ulvi; Lõo, Silva; Kolk, Anneli; Männamaa, Mairi; Talvik, Inga; Õiglane‐Shlik, Eve; Loorits, Dagmar; Talvik, Tiina; Ilves, Pilvi
Summary: Objective: With an incidence up to 63 per 100, 000 live births, perinatal stroke is an important cause of childhood epilepsy. The aim of the study was to find the prevalence of and predictive factors for epilepsy, and to describe the course of epilepsy in children with perinatal stroke with different vascular subtypes. Methods: Patients were retrieved from the Estonian Paediatric Stroke Database with follow‐up time at least 24 months. Patients were divided into 5 perinatal stroke syndromes: neonatal arterial ischemic stroke (AIS), neonatal hemorrhagic stroke, neonatal cerebral sinovenous thrombosis, presumed AIS, and presumed periventricular venous infarction. Results: The final study group included 73 children with perinatal stroke (39 boys). With a median follow‐up time of 8.6 years, epilepsy was diagnosed in 21/73 (29%) children, most of whom had AIS (17/21, 81%). The 18‐year cumulative poststroke epilepsy risk according to the Kaplan‐Meier estimator was 40.8% (95% confidence interval [CI] 20.7–55.9%). The median age at epilepsy diagnosis was 50 months (range 1 month to 18.4 years). Children with neonatal AIS had the highest risk of epilepsy, but children with presumed AIS more often had severe epilepsy syndromes. Cortical lesions (odds ratio [OR] 19.7, 95% CI 2.9–133), and involvement of thalamus (OR 9.8, 95% CI 1.8–53.5) and temporal lobe (OR 8.3, 95% CI 1.8–39.6) were independently associated with poststroke epilepsy. Significance: The risk for poststroke epilepsy after perinatal stroke depends on the vascular subtype. Patients with perinatal AIS need close follow‐up to detect epilepsy and start with antiepileptic treatment on time.